Economic Determinants Affecting Military Expenditures : Panel Data Analysis (Global Journal of Science Frontier Research, 2019)
Our research revolves around the topic of considering the military expenditures per capita as a dependent variable and the GDP per capita and CO2 Emissions per capita as two explanatory variables. The study is made up of ten sections addressing several points, each of which clarifies the research method in order to reach a conclusion revealing the importance of the findings. Beginning with the basic statistical characteristics, such as averages, standard deviations, minimums, maximums and the Compound Annual Growth Rate (CAGR), a benefit use of the graph of each variable for each country has been highlighted for a better understanding of the rising and falling during its temporal evolution. The various aspects of the panel analysis have been completed as the questions of individual specific heterogeneity in panel data, the panel unit root tests using the most famous from the first and second generations, and the co-integration analysis according to the Pedroni's approach, which has led to the rejection of the null hypothesis of no co-integration for each country and for the group as a whole.
Keywords: principal component analysis; panel co-integration; long-run equilibrium; forecasts